HubunganTeknik Menyusui dengan Risiko Terjadinya Mastitis pada Ibu Menyusui di Desa Kemuning Kecamatan Arjasa Kabupaten Jember (The Correlation between Breastfeeding Techniques and Risk of Mastitis at Kemuning Village of Arjasa Distrincts Jember Regency) - Armita Iriyana Hasanah; Ratna Sari Hardiani; Latifa Aini Susumaningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
The risk of mastitis is one of the problems that occurred during the breastfeeding process whichaffect the success of breast-milk. One of the factors that can increase the risk of mastitis isbreastfeeding techniques. The aim of this study was to analyze the relationship betweenbreastfeeding techniques and risk of mastitis in Kemuning village Arjasa districts, Jember. Thisresearch used an analytic survey design with cross sectional method. The subjects of this studywere breastfeeding’s mother who have infants age 0-6 months in Kemuning village. The samplingtechnique was a total sampling consist of 57 respondents. The instrument used observation sheet ofbreastfeeding techniques and questionnaires of mastitis risk. Result showed 36 respondents(63,2%) have feeding techniques in enough categories and 26 respondents (45,6%) have middlerisk of mastitis. The analysis based on statistical chi square by using CI=95% showed p value =0,005 (p value<α=0,05). It means that there was correlation between breastfeeding techniques andthe risk of mastitis. A better breastfeeding techniques will decrease the risk of mastitis. Healthworked need to improve the implementation of programs to provide information to mothers aboutbreastfeeding technique and the risk of mastitis.Keywords: Breastfeeding techniques, the risk of mastitis